New Paradigm of Applying Islamic Legal Principles in Contemporary Notary Practice in Indonesia - Lubis, Ikhsan; Siregar, Taufik; Lubis, Duma Indah Sari; Lubis, Andi Hakim (Andalas Law Journal, 2024)
This study explores the integration of Islamic legal principles into contemporary notarial practices in Indonesia, using a normative legal approach and qualitative methodology. It examines historical contributions, particularly from scholars such as Hilal ibn Yahya al-Bashri and Hajji Khalifah, who emphasized integrity, legal certainty, and ethical values in notarial law. The research investigates how these principles influence modern notarial roles under Law No. 2 of 2014. Findings highlight the importance of sharia compliance, ethics, and transparency in notarial duties, stressing that historical values remain essential for adapting to modern legal challenges.